Soil organic matter interactions along the elevation gradient of the James Ross Island (Antarctica) - Vlcek, Vitezslav; Juřička, David; Valtera, Martin; Dvořáčková, Helena; Štulc, Vojtěch; Bednaříková, Michaela; Šimečková, Jana; Váczi, Peter; Pohanka, Miroslav; Kapler, Pavel; Barták, Miloš; Enev, Vojtěch (Copernicus Publications, 2024)
Around half of the Earth’s soil organic carbon (SOC) is presently stored in the Northern permafrost region. In polar permafrost regions, low temperatures particularly inhibit both the production and biodegradation of organic matter. In such conditions, abiotic factors such as mesoclimate, pedogenic substrate or altitude are thought to be more important for soil development than biological factors. In Antarctica, biological factors are generally underestimated in soil development due to the rare occurrence of higher plants and the short time since deglaciation. In this study, we aim to assess the relationship between SOC and other soil properties related to the pedogenic factors or properties. Nine plots were investigated along the altitudinal gradient from 10 to 320 m at the deglaciated area of James Ross Island (Ulu Peninsula) with a parallel tea-bag soil proteins (EE-GRSP; Spearman r = 0.733, P=0.031) and the soil buffer capacity (expressed as a ΔpH; Spearman r = 0.817, P=0.011). The soil available P was negatively correlated with altitude (Spearman r = -0.711, P=0.032) and the exchangeable Mg was negatively correlated to the content of rock fragments (Spearman r = -0.683, P=0.050)No correlation was found between the available mineral nutrients (P, K, Ca, Mg) and SOC nor GRSP. This may be a consequence of the inhibition of biologically mediated nutrient cycling in the soil. Therefore, the main factor influencing nutrient availability in these soils decomposition experiment. SOC contents showed a positive correlation with the contents of easily extractable glomalin-related seems to be not the biotic, but rather the abiotic environment influencing the mesoclimate (altitude) or the level of weathering (rock content). Incubation in tea bags for 45 days resulted in the consumption and/or translocation of more labile polyphenolic and water-extractable organic matter, along with changes in C content (increase of up to +0.53 % or decrease of up to -1.31 % C) and a decrease in the C:N ratio (from 12.5 to 7.1–10.2), ...